2017
DOI: 10.1007/s00253-017-8522-z
|View full text |Cite
|
Sign up to set email alerts
|

Biobutanol production from apple pomace: the importance of pretreatment methods on the fermentability of lignocellulosic agro-food wastes

Abstract: Apple pomace was studied as a possible raw material for biobutanol production. Five different soft physicochemical pretreatments (autohydrolysis, acids, alkalis, organic solvents and surfactants) were compared in a high-pressure reactor, whose working parameters (temperature, time and reagent concentration) were optimised to maximise the amount of simple sugars released and to minimise inhibitor generation. The pretreated biomass was subsequently subjected to a conventional enzymatic treatment to complete the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 47 publications
(66 reference statements)
1
47
0
Order By: Relevance
“…Although no significant (p > 0.05) difference was found within different acid or alkali pretreatments, the acid pretreatment groups had a higher glucose production compared with the alkali pretreatment groups on average. A similar result was found in a previous study that alkali (sodium hydroxide and potassium hydroxide) was not as effective as acids (sulfuric acid, hydrogen chloride, and nitric acid) to pretreat apple pomace for the production of hydrolyzed sugars [13]. We further investigated the synergistic cooperation of cellulase and pectinase for the glucose production during hydrolysis.…”
Section: Hydrolyzed Sugars Productionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although no significant (p > 0.05) difference was found within different acid or alkali pretreatments, the acid pretreatment groups had a higher glucose production compared with the alkali pretreatment groups on average. A similar result was found in a previous study that alkali (sodium hydroxide and potassium hydroxide) was not as effective as acids (sulfuric acid, hydrogen chloride, and nitric acid) to pretreat apple pomace for the production of hydrolyzed sugars [13]. We further investigated the synergistic cooperation of cellulase and pectinase for the glucose production during hydrolysis.…”
Section: Hydrolyzed Sugars Productionsupporting
confidence: 80%
“…As can be seen in Table 2, the contents of degradation products (inhibitors) including HMF and furfural are significantly (p < 0.05) higher in liquids after acid pretreatment and hydrolysis than those in liquids after alkali pretreatment and hydrolysis. A previous study found that the apple pomace hydrolysate obtained after nitric acid pretreatment and enzymatic hydrolysis was not fermentable and the possible reason was the high content of inhibitors generated in the acidic treatment [13]. At last, a total of 9.6 and 9.4 g/L of ABE were generated by consumption of 30.4 and 28.0 g/L of total sugars from ACHS and ALHS, respectively.…”
Section: Abe Productionmentioning
confidence: 96%
See 1 more Smart Citation
“…The biomasses were ground in a SM100 Comfort rotary mill (Retsch GmbH, Haan, Germany), sieved to a size of 0.5-1.0 mm and stored at room temperature in airtight containers until being used. Moisture, ash, cellulose, hemicellulose, Klason lignin, protein and fat were determined as described by Hijosa-Valsero et al [18]. Starch was determined by polarimetry according to Spanish national regulations [19].…”
Section: Biomass Description and Processingmentioning
confidence: 99%
“…Thereby, twelve different chemical reagents: acids (H2SO4, HCl, HNO3), alkalis (NaOH, KOH, NH4OH), organic solvents (ethanol, methanol, acetone) and surfactants (Tween 80, PEG 6000, and CTAB) were compared to select the most efficient reagent in each group. Hydrolysis experiments were performed as previously described [18]. The hydrolysates obtained were analyzed for sugars (cellobiose, glucose, xylose, rhamnose and arabinose), organic acids (formic acid, acetic acid and levulinic acid), 5-HMF and furfural, using an Agilent 1200 HPLC equipment (Agilent Technologies) furnished with an Aminex HPX-87H (Biorad, Hercules, CA, USA) and a Refractive Index Detector (RID) G1362A (Agilent Technologies) as described by Hijosa-Valsero et al [18].…”
Section: Hydrolysate Preparation and Chemical Analysismentioning
confidence: 99%